Maths Bertell, Mr. Frog & Kendra Willson (eds.), Contacts and Networks in the Baltic Sea Region. Austmarr as a Northern Mare nostrum, ca. 500–1500 AD - Cederbom, Charlotte (Historisk Tidskrift för Finland, 2021)
-